Nieborow - Piwkowski, Wlodzimierz; Jablonski, Krzysztof (Warszawa : Arkady, 1978)
A guide to the 17th century palace west of Warsaw.
Summary in English, French, German, and Russian; list of illustrations also in English, French, German, and Russian.
Keywords: Palac w Nieborowie (Nieborow, Poland) -- Guidebooks; Nieborow (Poland) -- Guidebooks